Case Study of Tribal Farmers' Agricultural Information Needs and Accessibility in Attappady Tribal Block, Palakkad - Jalaja .V and Kala. P A (IOSR Journal Of Humanities And Social Science, 2015)
This paper highlights agricultural information needs of tribal farmers in Attappady Tribal Block, Palakkad District, Kerala. Tribal farmers play an immeasurable role in agricultural production. This study investigated how tribal farmers access and use information in their Agricultural field to attain food security. The study sought to establish the farming activities of the tribal farmers ,ascertain their information needs, their information seeking behavior, establish information sources, channels of information and the problems they face while seeking information and suggest ways for improvement. A survey is carried out on the 150 tribal farmers of the 3 panchayats, 50 tribal farmers from each panchayat of Attappady Tribal Block. Palakkad District, Kerala, but only data for 131 respondents were analyzed.